International Financial Reporting Standard (IFRS): The Awareness Level In Accounting Student - Dewi, Ayu Aryista; Dewi, Luh Gede Krisna (UNIVERSITAS NEGERI SURABAYA, 2019)
Changes in accounting standards currently referring to International Financial Reporting Standards (IFRS) require substantive changes at the tertiary level. The purpose of this study is to examine the differences in the level of awareness of accounting students proxied by the level of understanding, knowledge, interest, learning method preferences (pedagogy), and expected expectations (outcomes) of students towards IFRS. Research respondents were S1 students of the Accounting Study Program regular class and an English class. The analysis was carried out through questionnaires. The analysis tool uses independent t-test with the SPSS program. The results of the study indicate that there are differences in the level of interest (interest) and the desired level of expectations (outcomes) in IFRS learning. Research implications are expected to contribute to universities in the preparation of curriculum and formulate learning strategies to improve the knowledge and readiness of accounting students regarding the application of IFRS